2002
DOI: 10.1016/s0028-3932(01)00126-9
|View full text |Cite
|
Sign up to set email alerts
|

Implicit memory varies across the menstrual cycle: estrogen effects in young women

Abstract: Evidence that ovarian steroid hormones such as estrogen and progesterone affect cognition comes from studies of memory in older women receiving estrogen replacement therapy and studies of sexually dimorphic skills in young women across the menstrual cycle. Sixteen women (ages 18-28) completed tests of memory (implicit category exemplar generation, category-cued recall, implicit fragmented object identification) and sexually dimorphic skills (fine motor coordination, verbal fluency, mental rotations) at the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
209
3
13

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(241 citation statements)
references
References 47 publications
16
209
3
13
Order By: Relevance
“…Although our study sample size does not permit to draw firm conclusions about the role of gender in this type of motor learning, women appeared to perform significantly worser than men in our motor-adaptation task, in accordance with the findings of Sawaki et al (2003), who reported gender differences on a simple motor-learning paradigm using flexion-extension thumb movements. Also, it lends support to the hypothesis that female hormones may modulate neural plasticity and motor-skill learning (Maki et al, 2002;Smith et al, 1999). In our study, however, while gender may have modulated motor learning differently, it cannot explain the significant differences between amantadine low-performance and placebo low-performance subgroups, which are matched for sex distribution.…”
Section: Discussionsupporting
confidence: 71%
“…Although our study sample size does not permit to draw firm conclusions about the role of gender in this type of motor learning, women appeared to perform significantly worser than men in our motor-adaptation task, in accordance with the findings of Sawaki et al (2003), who reported gender differences on a simple motor-learning paradigm using flexion-extension thumb movements. Also, it lends support to the hypothesis that female hormones may modulate neural plasticity and motor-skill learning (Maki et al, 2002;Smith et al, 1999). In our study, however, while gender may have modulated motor learning differently, it cannot explain the significant differences between amantadine low-performance and placebo low-performance subgroups, which are matched for sex distribution.…”
Section: Discussionsupporting
confidence: 71%
“…Some studies observed performance differences over the menstrual cycle in tasks measuring spatial and verbal abilities as well as memory (Hampson, 1990;Hausmann et al, 2000;Maki et al, 2002;Rosenberg and Park, 2002), domains that are known to be related to hippocampal function (KĂŒhn and Gallinat, 2014). However, some studies report no cyclerelated variations in performance on verbal and visuospatial tests (e.g., Epting and Overman, 1998;Gordon and Lee, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown cognitive differences between women in the early follicular phase when hormones are low (i.e., menses) compared with other phases of the menstrual cycle , Maki et al, 2002. For example, one study found that spatial abilities were increased in women during the early follicular phase, whereas fine motor skills and verbal fluency were enhanced during the mid-luteal phase .…”
Section: Introductionmentioning
confidence: 99%